Impact of feeding levels on growth performance and food conversion of Acanthopagrus arabicus cultivated in concrete tanks at Basrah province - Yesser, Abdul-Karim T.; Al-Faiz, Nawras A.; Hussein, Sadek A. (Iraqi Journal of Aquaculture, 2021)
This study was conducted to determine the effect of various feeding levels (3%, 5% and 7% body weight/ day) on final weight, weight gain, specific and daily growth rates as well as food conversion rate of Arabian yellowfin seabream Acanthopagrus arabicus. The experiment were executed in three concrete tanks (1m3) and extended 60 days. Results reveal significant differences (P>0.05) of final weight, weight gain, specific and daily growth rates at different feeding levels. Final weight attain 61.9, 63.25 and 61.65gm in feeding levels 3, 5, 7% body weight, respectively. The best food conversion rate showed that feed conversion rate value (4.677) was encountered at the feeding level 3% body weight followed by feeding ratio 5% (7.654) where as the lower food conversion rate (11.018) was found at the feeding level 7% body weight, Statistical analysis proved significant differences (P<0.05) in food conversion rates among selected feeding levels.